Water-based anticorrosive paint with photoelectric cathode protection performance and preparation method of water-based anticorrosive paint

By combining CeO2/FeWO4/CdIn2S4 nanoscale composite materials with polymerization-grade high-efficiency suspension and stable emulsification and thickening components, the problem of low photoelectric conversion efficiency of photocathode protection materials and prone to defects in aqueous coatings is solved, and efficient photocathode protection and excellent corrosion resistance are achieved.

CN119912853APending Publication Date: 2025-05-02SHIJIAZHUANG TIEDAO UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510054513.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, the photoelectric conversion efficiency of photocathode protection materials is low, and water-based coatings are prone to pinholes and defects, which affects the anticorrosion performance.

Method used

CeO2/FeWO4/CdIn2S4 nano-level composite material is combined with polymeric high-efficiency suspension and stable emulsification thickening components, and nano-level composite material is prepared by solvent-heat-hydrothermal precipitation method, and it is uniformly dispersed in the aqueous polymer film-forming substance to form a dense passivation layer.

Benefits of technology

It significantly improves the photoelectric conversion efficiency and corrosion resistance of water-based anti-corrosion coatings, enhances the dispersion and stability of the coatings, and improves the anti-corrosion and crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912853A_ABST
    Figure CN119912853A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based anti-corrosion coating with photoelectric cathode protection performance and a preparation method of the water-based anti-corrosion coating. The coating is prepared from a water-based polymer emulsion, deionized water, a CeO2 / FeWO4 / CdIn2S4 nano composite material, a polymer-grade efficient suspension stable emulsification thickening component, a curing agent, a defoaming agent, a flatting agent, an adhesion promoter, polyamide wax powder and cationic guar gum powder. The preparation method comprises the following steps: firstly synthesizing CeO2 and FeWO4 nano powder, then preparing a CeO2 / FeWO4 / CdIn2S4 composite material through a hydrothermal reaction, then preparing the emulsifying and thickening component, and finally mixing all the components to prepare the coating. According to the coating, photo-induced electrons are generated by utilizing a semiconductor material under illumination, so that photoelectric cathode protection of a metal matrix is realized, meanwhile, micropores of the coating are filled, and the compactness and physical properties of the coating are enhanced. Compared with the prior art, the coating disclosed by the invention has more excellent corrosion resistance, good adhesive force and durability and high environmental protection property, is suitable for various corrosion prevention fields, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectric cathode protection composite materials and anticorrosion coatings, in particular to a water-based anticorrosion coating with photoelectric cathode protection performance. Background Art

[0002] The corrosion of steel structures has brought huge economic losses and safety hazards, and countless resources are wasted every year due to metal corrosion. In order to inhibit metal corrosion, photocathode protection (PECP) technology has been developed, using PECP materials to absorb solar energy to generate photogenerated electrons and transfer them to the metal surface, thereby playing a role in cathodic protection. The basic principle of this technology is to use semiconductor materials to generate photogenerated electrons and hole pairs under light conditions, transfer the photogenerated electrons to the base metal material, and achieve a protection effect similar to that of an applied cathode current. The advantage of PECP technology is that it does not use toxic and harmful substances, does not generate waste, prevents pollution at the source, and is green and environmentally friendly.

[0003] However, the application and expansion of PECP materials need to be combined with organic coatings to achieve the synergistic corrosion protection and large-scale application of PECP and organic coatings, which is an important link in the application of PECP materials in metal corrosion protection. Among the existing PECP composite materials, CeO2 (cerium oxide) is widely regarded as an ideal photocathodic protection material due to its non-toxicity, low cost and high photoelectric reaction activity, and is also a good corrosion inhibitor oxide. However, the band gap of single CeO2 material is relatively wide, resulting in low photoelectric conversion efficiency and unsatisfactory PECP performance. In order to solve this problem, FeWO4 was introduced as a P-type semiconductor material due to its large specific surface area, strong visible light absorption ability and high charge separation efficiency, forming a heterojunction with N-type semiconductor CeO2 to improve the separation efficiency of photogenerated charges.

[0004] In addition, CdIn2S4 (cadmium indium sulfide) is a thio-bimetallic photocatalyst with a narrow band gap, suitable electronic structure and band gap, excellent visible light responsiveness, simple preparation process and low cost. Compounding CdIn2S4 with CeO2 and FeWO4 can not only narrow the band gap, but also form an NPN type heterojunction gradient energy level, effectively absorb visible light, promote the rapid separation of photogenerated electrons and holes through the built-in electric field, thereby improving the photoelectric conversion efficiency and further improving the PECP performance of the composite material.

[0005] At the same time, water-based coatings have become an inevitable trend in the development of green and environmentally friendly coatings because they contain less or no volatile organic compounds (VOCs). However, water-based coatings composed solely of resin matrices are prone to pinholes and defects after film formation, curing and long-term service. These pinholes and defects not only reduce the physical barrier properties of the coating, but may also affect the dispersibility and stability of PECP materials, thereby affecting the anti-corrosion performance. Therefore, in order to improve the overall performance of water-based anti-corrosion coatings, it is urgent to effectively combine PECP materials with organic coatings to ensure the integrity and anti-corrosion performance of the coating.

[0006] In summary, the existing technology has made certain progress in using PECP materials for metal corrosion protection, but there are still shortcomings in improving the photoelectric conversion efficiency, optimizing the performance of PECP, and ensuring the film quality and long-term stability of water-based coatings.

[0007] Therefore, there is an urgent need to develop a new anti-corrosion coating that can effectively combine PECP materials with water-based organic coatings to solve the above-mentioned problems in the prior art. Summary of the invention

[0008] The purpose of the present invention is to provide a water-based anti-corrosion coating with photoelectric cathode protection performance, which has the advantages of high-efficiency dispersion stability, excellent photoelectric conversion efficiency, outstanding anti-corrosion durability and environmental protection, and solves the problems of low photoelectric conversion efficiency of photoelectric cathode protection materials and easy generation of pinholes and defects in water-based coatings in the prior art.

[0009] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a water-based anti-corrosion coating with photoelectric cathode protection performance, the coating comprising two components A and B, wherein: component A comprises the following raw materials in parts by mass: 60-70 parts of water-based polymer emulsion film-forming material; 5-20 parts of deionized water; 20-30 parts of polymerization-grade high-efficiency suspended stable emulsifying thickening component; 10-30 parts of curing agent; 1.5-3 parts of defoaming agent; 1-2 parts of leveling agent; 1.5-3 parts of adhesion promoter; 0.5-2 parts of polyamide wax powder; 0.1-0.5 parts of cationic guar gum powder; component B is 8-16 parts of CeO2 / FeWO4 / CdIn2S4 photoelectric cathode protection component in parts by mass.

[0010] Preferably, the aqueous polymer emulsion film-forming substance is selected from at least one of aqueous epoxy resin, aqueous epoxy-modified polyurethane, aqueous epoxy acrylic emulsion, or a mixed emulsion of two thereof, and the mass ratio of the mixed emulsion is 1:1-1:15.

[0011] Preferably, the curing agent is selected from one of CYDHD-220, CYDHD-593, triethylenetetramine, diethylenetriamine, T31, or a mixture of two of them, and the mass ratio of the mixture is 1:1-1:4.

[0012] Preferably, the defoamer is selected from at least one or a mixture of two of Foamaster MO 2134 mineral oil defoamer, TEGO AIREX 902W defoamer, YT-50B high-efficiency defoamer, DL-272 water-based defoamer, DL-14 coating defoamer, HY-1040A defoamer and BYK-054 defoamer, and the mass ratio of the mixture is 1:1-1:4.

[0013] Preferably, the leveling agent is an organic silicon leveling agent, selected from at least one of BYK-306, BYK-333 leveling agent, 3322 hyperbranched polyether water-oil universal leveling agent, water-based emulsion leveling agent 2020, TEGO4100 leveling agent and Glide 450 leveling agent, or a mixture of two thereof, and the mass ratio of the mixture is 1:1-1:4.

[0014] Preferably, the adhesion promoter is selected from at least one of KH-550, KH-560 and KH-570.

[0015] Preferably, the polymer-grade high-efficiency suspension stable emulsifying thickening component is selected from at least one of methoxy polyethylene glycol (MPEG), maleic anhydride, trimethylolpropane trimethacrylate, p-toluenesulfonic acid, sodium dodecyl sulfate, thiosemicarbazide, lauryl alcohol polyoxyethylene ether, ammonium persulfate, unsaturated organic silane monomer, allyl polyoxyethylene polyoxypropylene ether, methyl-allyl polyoxyethylene ether, and methoxy polyethylene glycol acrylate;

[0016] The methoxy polyethylene glycol (MPEG) is selected from at least one of MPEG-200, MPEG-350, MPEG-750, MPEG-1000 and MPEG-2000, or a mixture of two of them in a mass ratio of 1:1.

[0017] Preferably, the unsaturated organosilane monomer is selected from at least one of dimethyl (dimethylamino) vinyl silane, allyl trimethyl silane, 3-allyloxypropyl trimethoxy silane, methacryloxypropyl trimethoxy silane, vinyl trimethoxy silane, allyl trimethyl silane, 3-allyloxypropyl trimethoxy silane, methacryloxy-propyl trimethoxy silane (KH570), and methylallyl-propyl trimethoxy silane, or a mixture of two of them in a mass ratio of 1:1-4:1.

[0018] A method for preparing a water-based anticorrosive coating having photocathodic protection performance comprises the following steps:

[0019] Preparation of S1, CeO2 / FeWO4 / CdIn2S4 photocathodic protection components:

[0020] S11: 1-5 parts of 2M Ce(NO3)3 solution and 1-5 parts of 2M NaOH solution are mixed, 0.1-0.2 parts of sodium dodecyl sulfate are added, the mixture is evenly mixed, and the mixture is heated to 90-120°C for solvent thermal reaction for 2-3 hours. The obtained powder is washed with deionized water for 3-4 times, and then washed with anhydrous ethanol for 3-4 times. Finally, the powder is vacuum sintered at 120-150°C for 2-3 hours to obtain CeO2 nanopowder with a particle size of 20-200 nanometers.

[0021] S12: adding 2-6 parts of 3M Fe(NH4)2·(SO4)2·6H2O solution to 2-6 parts of 3M Na2WO4·2H2O aqueous solution and mixing them evenly, adding 0.01-0.05 parts of 1M NaOH solution to adjust the pH of the mixture to 8.0-9.5, placing the reaction mixture in an autoclave, reacting at 160-180°C for 8-12 hours, filtering the obtained slurry, washing it with deionized water for 3-5 times, and vacuum drying it at 60-80°C for 5-6 hours to obtain FeWO4 nanopowder with a particle size of 10-150 nanometers;

[0022] S13: ultrasonically suspending the CeO2 nanopowder obtained in step S11 and the FeWO4 nanopowder obtained in step S12 in 50-120 parts of anhydrous ethanol in a ratio of 20-50 parts and 20-50 parts to obtain a suspension A;

[0023] S14: Dissolve 5-15 parts of InCl3·4H2O and 4-8 parts of Cd(NO3)2·4H2O in 30-60 parts of deionized water, add 10-20 parts of thiosemicarbazide, then add 0.2-0.5 parts of methylallyl-propyltrimethoxysilane and 0.01-0.05 parts of lauryl alcohol polyoxyethylene ether, stir for 1-2 hours to mix evenly, and obtain a milky white suspension B; add suspension A to suspension B and mix evenly, then transfer to a high-pressure reactor, perform hydrothermal reaction at 150-190°C for 4-6 hours, filter the obtained solid product, wash with anhydrous ethanol 3-5 times, and finally vacuum dry at 80-100°C for 3-5 hours to obtain a CeO2 / FeWO4 / CdIn2S4 nano-composite material with a particle size of 80-280 nanometers.

[0024] Preferably, the method further comprises:

[0025] S2. Preparation of polymer-grade high-efficiency suspension stable emulsification thickening component:

[0026] S21: 8-15 parts of methoxy polyethylene glycol (MPEG), 10-20 parts of maleic anhydride and 3-5 parts of trimethylolpropane trimethacrylate are weighed according to weight ratio, added into a reactor, and stirred at 120-200 r / min at 90-120° C. for 5-20 minutes to fully mix and melt the reactants;

[0027] S22: adding 0.1-0.5 parts of p-toluenesulfonic acid, raising the temperature to 120-140° C. and continuing the reaction for 2-5 hours;

[0028] S23: then add 3-5 parts of a mixture of allyl polyoxyethylene polyoxypropylene ether and methyl-allyl polyoxyethylene ether in a mass ratio of 1:1, 0.1-1.3 parts of an unsaturated organic silane monomer and 3-5 parts of methoxy polyethylene glycol acrylate, and continue to stir evenly;

[0029] S24: adding 20-40 parts of deionized water and mixing evenly, then adding 0.05-0.2 parts of ammonium persulfate initiator aqueous solution, and reacting for 2-4 hours;

[0030] S25: After naturally cooling to room temperature, the pH of the mixture is adjusted to 6-7 with a pH regulator to obtain a polymer-grade high-efficiency suspension stable emulsification thickening component;

[0031] S3. Preparation of water-based anticorrosive coating with photoelectric cathode protection:

[0032] S31: 60-70 parts of aqueous polymer emulsion film-forming substance, 5-20 parts of deionized water, 20-30 parts of polymer-grade high-efficiency suspension stable emulsifying thickening component, 10-30 parts of curing agent, 1.5-3 parts of defoaming agent, 1-2 parts of leveling agent, 1.5-3 parts of adhesion promoter, 0.5-2 parts of polyamide wax powder and 0.1-0.5 parts of cationic guar gum powder are added into a container according to the mass parts, and dispersed at a high speed at a stirring rate of 200-300 r / min for 0.5-2 hours;

[0033] S32: adding 4-12 parts of nanometer photocathode protection component, and dispersing at a high speed of 300-500 r / min for 0.5-2 hours;

[0034] S33: Add 10-50 parts of curing agent within 2-5 hours before use, and stir at a rate of 120-300 r / min for 1-2 hours to obtain a water-based anti-corrosion coating with photocathodic protection performance.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The present invention achieves the effect of improving the photoelectric cathode protection performance of water-based anticorrosive coatings by setting CeO2, FeWO4 and CdIn2S4 semiconductor materials as photoelectric cathode protection components and combining them with polymer-grade efficient suspension stable emulsification thickening components. CeO2 is non-toxic, low-cost and has high photoelectric reaction activity, FeWO4 has a large specific surface area and high charge separation efficiency, and CdIn2S4 improves the photoelectric conversion efficiency and PECP performance by narrowing the band gap and forming an NPN heterojunction, which significantly enhances the overall corrosion resistance of the coating.

[0037] 2. The present invention achieves the effect of eliminating interfacial tension and reducing agglomeration and aggregation by synthesizing an efficient slurry stable dispersion component containing an organic silicon surface enhancer and polyoxyethylene polyoxypropylene ether alcohol. The thickening component is generated by the esterification reaction of MPEG with trimethylolpropane trimethacrylate and maleic anhydride to form an unsaturated methoxy polyethylene glycol ester, which is grafted into methylolpropane trimethacrylate containing unsaturated double bonds, and further copolymerized with unsaturated polyether and organic silane monomers to form a thickening component with non-ionic surface activity and efficient dispersion stability. This effectively improves the dispersibility and compatibility of the photoelectric cathode protection material in the epoxy coating, prevents the aggregation and precipitation of the material, and enhances the stability and durability of the coating.

[0038] 3. The present invention applies CeO2 / FeWO4 / CdIn2S4 nanocomposite materials to a water-based anticorrosive coating system, achieving the effect of improving the anticorrosion durability and crack resistance of the coating. Under the action of a polymer-grade efficient suspension stable emulsification thickening component, the composite material has good dispersibility, suspension stability and compatibility with water-based resins. Through the synergistic effect of each component, the composite material achieves physical barrier, slow release, anticorrosion and photoelectric cathode protection functions, significantly improving the overall protective performance of the coating.

[0039] 4. The present invention achieves the effect of forming a dense passivation layer, enhancing the adhesion of the coating and improving the corrosion resistance of the metal by introducing nano-semiconductor materials and organic silicon surface enhancers into the water-based polymer film-forming material. CeO2 / FeWO4 / CdIn2S4 nano-semiconductor materials block the pinholes of the coating to prevent the intrusion of moisture and corrosive electrolytes, and work together with the organic silicon surface enhancer to form a dense and uniform network structure. This not only enhances the adhesion of the coating to the metal surface, but also isolates the corrosive medium by forming a passivation layer, significantly improving the corrosion resistance of the steel bars and the long-term durability of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1(a) is a comparison diagram of open circuit potential (OCP) of pure CeO2, CeO2 / FeWO4 and CeO2 / FeWO4 / CdIn2S4 photocathode protection composite materials according to Example 4 of the present invention;

[0041] Figure 2 (a) is a schematic diagram of the open circuit potential (OCP) of the composite of CeO2 / FeWO4 / CdIn2S4 / water-based coating with different addition amounts of the present invention and (b) pure water-based coating;

[0042] Figure 3 Schematic diagram of the Tafel polarization curves of 304SS, pure water-based coating and CeO2 / FeWO4 / CdIn2S4 / water-based coating series of the present invention (a) under visible light and (b) under dark state;

[0043] Figure 4 A schematic diagram of the composition and mass fraction of a water-based anticorrosive coating having photoelectric cathode protection performance according to the present invention;

[0044] Figure 5 The present invention is a flow chart of a method for preparing a water-based anticorrosive coating with photocathodic protection performance. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] See also Figures 1 to 5 In view of the problems of insufficient photoelectric cathode protection performance, poor coating density and environmental pollution in the prior art anti-corrosion coatings, the present invention provides a water-based anti-corrosion coating with photoelectric cathode protection performance and a preparation method thereof. Through a carefully designed composite material structure and an optimized coating formula, the present invention achieves efficient photoelectric cathode protection effect and excellent anti-corrosion performance, while having good environmental protection characteristics. Specifically including:

[0047] 1. Preparation of photoelectric cathode protection materials:

[0048] Composite material selection: Three semiconductor materials, CeO2 (cerium oxide), FeWO4 (ferrous tungstate) and CdIn2S4 (cadmium indium sulfide), were selected to construct the ternary composite material CeO2 / FeWO4 / CdIn2S4. Preparation method: The solvent thermal-hydrothermal precipitation method was used to control the reaction conditions to ensure the efficient compounding of the three materials and form a composite material with excellent photoelectric properties. Among them, the solvent thermal-hydrothermal precipitation method was used to prepare the CeO2 / FeWO4 / CdIn2S4 composite material. The specific steps are as follows: Preparation of CeO2 nanopowder: 2MCe(NO3)3 solution and 2M NaOH solution were mixed in a certain proportion, sodium dodecyl sulfate was added as a surfactant, and the pH was adjusted to an appropriate range. The reaction was carried out under solvent thermal conditions (such as 90°C) for 2 hours to generate CeO2 nanopowder. Through the steps of washing, filtering and vacuum sintering, high-purity and uniform particle size CeO2 nanopowder (particle size of about 20nm) was obtained. Preparation of FeWO4 nanopowder: Mix Fe(NH4)2·(SO4)2·6H2O solution with Na2WO4·2H2O aqueous solution, add appropriate amount of NaOH solution to adjust pH to 8.0-9.5. Perform hydrothermal reaction in a high pressure reactor (e.g., 160°C, 8 hours) to generate FeWO4 nanopowder. High purity FeWO4 nanopowder is obtained by washing and vacuum drying.

[0049] Preparation of CeO2 / FeWO4 composite nanopowder: CeO2 nanopowder and FeWO4 nanopowder were mixed in proportion and suspended in anhydrous ethanol by ultrasonication to ensure that the two materials were fully dispersed to form a uniform suspension A.

[0050] Preparation of CdIn2S4 nanocomposite materials: InCl3·4H2O and Cd(NO3)2·4H2O were dissolved in deionized water, and surfactants such as thiosemicarbazide, methylallyl-propyltrimethoxysilane and lauryl alcohol polyoxyethylene ether were added and stirred evenly to obtain a milky white suspension B. Suspension A was added to suspension B, and after mixing evenly, the mixture was transferred to a high-pressure reactor. The hydrothermal reaction was carried out at 150°C for 4 hours. After the reaction was completed, a CeO2 / FeWO4 / CdIn2S4 nanocomposite material with a particle size of 80 nm was obtained by filtering, washing and vacuum drying.

[0051] The present invention selects environmentally friendly water-based epoxy resin and water-based epoxy modified polyurethane as the main film-forming material matrix to ensure the green and environmentally friendly characteristics of the coating. In order to improve the rheological properties and suspension stability of the coating, a polymer-grade high-efficiency suspension stable emulsifying thickening component is added.

[0052] Preparation of polymerization-grade efficient suspension stable emulsification thickening component: Esterification reaction: Weigh methoxy polyethylene glycol (such as MPEG-750), maleic anhydride and trimethylolpropane trimethacrylate according to the weight ratio and add them to the reactor. Heating and stirring: Stir at 120r / min for 5 minutes at 90°C to fully mix and melt the reactants. Catalyst addition: Add p-toluenesulfonic acid as a catalyst, raise the temperature to 120°C, and continue the reaction for 2 hours. Copolymerization reaction: Then add a mixture of allyl polyoxyethylene polyoxypropylene ether and methyl-allyl polyoxyethylene ether, as well as unsaturated organic silane monomers, and carry out copolymerization to generate a polymerization-grade efficient suspension stable emulsification thickening component. Aqueous phase polymerization: Add deionized water and mix evenly, then add an aqueous solution of ammonium persulfate initiator, and carry out aqueous phase polymerization for 2 hours.

[0053] pH adjustment: After naturally cooling to room temperature, the pH of the mixture is adjusted to 6-7 with a pH adjuster to obtain a polymer-grade high-efficiency suspension stable emulsification thickening component.

[0054] 2. Selection and modification of water-based film-forming material matrix:

[0055] Base material: Environmentally friendly water-based epoxy resin and water-based epoxy modified polyurethane are selected as the main film-forming materials to ensure the green and environmentally friendly characteristics of the coating. Thickening component: The introduction of polymer-grade high-efficiency suspension stable emulsification thickening component, through the polymer structure generated by chemical reaction, improves the rheology and stability of the coating and prevents the agglomeration and precipitation of inorganic components.

[0056] 3. Dispersion and stability of composite materials in aqueous matrix:

[0057] Interface adjustment: Use polymer-grade high-efficiency suspension stable emulsification thickening components to eliminate the interfacial tension between the CeO2 / FeWO4 / CdIn2S4 composite material and the water-based polymer matrix to ensure its uniform dispersion. Micropore filling: In the dark state, the composite material fills the micropores of the water-based resin film-forming material, enhances the density and physical barrier of the coating, and prevents the intrusion of corrosive media.

[0058] Under light conditions, the semiconductor material in the composite material absorbs light energy and generates photogenerated electrons and holes. The heterojunction structure promotes the rapid separation of electrons and holes, and the photogenerated electrons migrate to the surface of the metal matrix, providing cathodic protection and inhibiting the anodic corrosion of the metal. Under no light conditions: Even under no light conditions, the composite material provides continuous anti-corrosion protection by extending the diffusion path of corrosive ions through physical barrier effect.

[0059] In this solution, auxiliary materials include: Corrosion inhibitor: polyamide wax powder and cationic guar gum powder are used as corrosion inhibitors to further improve the corrosion inhibition performance and suspension stability of the coating. Defoamer and leveling agent: ensure the uniformity and surface flatness of the coating during preparation and application. Adhesion promoter: enhance the bonding force between the coating and the metal substrate to prevent the coating from falling off.

[0060] Photocathodic protection is a technology that uses semiconductor materials to generate photogenerated electrons under light conditions and inhibits the corrosion of metal substrates through electron migration. The specific mechanism is as follows: Photogenerated electron generation: When the CeO2 / FeWO4 / CdIn2S4 composite material is exposed to light, the semiconductor material absorbs light energy, and the electrons transition from the valence band to the conduction band, generating photogenerated electrons and holes. Electron separation and migration: CeO2 is an N-type semiconductor, FeWO4 is a P-type semiconductor, and CdIn2S4 has a narrow band gap. By forming an NPN heterojunction, it promotes the rapid separation of electrons and holes and reduces charge recombination. Cathodic protection: The generated photogenerated electrons migrate to the surface of the metal substrate through the built-in electric field, forming an electron flow, reducing the corrosion potential of the metal substrate, and inhibiting the anodic corrosion reaction of the metal. Continuous protection: In the absence of light, the composite material prolongs the diffusion path of corrosive ions through physical barriers, providing continuous anti-corrosion protection.

[0061] Mixing and preparation of water-based anticorrosive coatings, mixing of base coatings: add water-based epoxy resin emulsion, water-based epoxy modified polyurethane, polymer-grade high-efficiency suspension stable emulsifying thickening component, deionized water, defoamer, leveling agent and adhesion promoter components in the container in sequence. High-speed stirring: through high-speed stirring, ensure that each component is evenly dispersed to form a uniform coating matrix. Add photocathodic protection components: Finally, add CeO2 / FeWO4 / CdIn2S4 nano-composite materials, polyamide wax powder and cationic guar gum powder, and continue to stir evenly to ensure that the nano-composite materials are evenly dispersed in the water-based matrix. Add curing agent: before the coating is used, add curing agent for cross-linking reaction to form a water-based anticorrosive coating with high adhesion and corrosion resistance.

[0062] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. The above materials are preferably high-purity raw materials, such as purity ≥ 99.5%, or analytically pure, to ensure the quality of the obtained composite material.

[0063] Embodiment 1:

[0064] Preparation of S1, CeO2 / FeWO4 / CdIn2S4 Photocathodic Protection Components

[0065] S11, 1 part of 2M Ce(NO3)3 solution and 1 part of 2M NaOH solution were mixed, 0.1 part of sodium dodecyl sulfate was added, and the mixture was heated to 90°C for solvent thermal reaction for 2 hours. The obtained powder was washed with deionized water 3 times and anhydrous ethanol 3 times, and then the solid was vacuum sintered at 120°C for 2 hours to obtain CeO2 nanopowder with a particle size of 20nm;

[0066] S12. Add 2 parts of 3M Fe(NH4)2·(SO4)2·6H2O solution to 2 parts of 3M Na2WO4·2H2O aqueous solution and mix well. Add 0.01 parts of 1M NaOH solution and adjust the pH of the mixture to 8.0. Place the reaction mixture in a high-pressure reactor at 160°C for 8 hours, filter the obtained slurry, wash with deionized water 3 times, and vacuum dry at 60°C for 5 hours to obtain nano-FeWO4 powder with a particle size of 10 nm.

[0067] S13, 20 parts of the nanomaterials obtained from S1 and 20 parts of S2 are ultrasonically suspended in 50 parts of anhydrous ethanol to obtain a suspension A.

[0068] S14, dissolve 5 parts of InCl3.4H2O and 4 parts of Cd(NO3)2.4H2O in 30 parts of deionized water and stir evenly, add 10 parts of thiosemicarbazide, add 0.2 parts of methylallyl-propyl trimethoxysilane, and 0.01 parts of lauryl alcohol polyoxyethylene ether and stir for 1 hour to mix evenly, and obtain a milky white suspension B, then add the suspension A obtained in step S3 to the suspension B and mix evenly, transfer to a high-pressure reactor and heat to 150°C for hydrothermal reaction for 4 hours, filter the obtained solid product, wash it 3 times with anhydrous ethanol, and dry the washed solid at 80°C in vacuum for 3 hours to obtain a nano-scale CeO2 / FeWO4 / CdIn2S4 photocathode protection anticorrosion reinforced composite material. The particle size is 80nm.

[0069] S2. Preparation of polymer grade high efficiency suspension stable emulsifying thickening component

[0070] 8 parts of methoxy polyethylene glycol MPEG-750 and 10 parts of maleic anhydride and 3 parts of trimethylolpropane trimethacrylate were weighed by weight, added into a reactor, stirred at 120r / min for 5 minutes at 90°C to fully mix and melt the reactants, added 0.1 parts of p-toluenesulfonic acid, heated to 120°C and reacted for 2 hours, then added 3 parts of a mixture of allyl polyoxyethylene polyoxypropylene ether and methyl-allyl polyoxyethylene ether in a mass ratio of 1:1, 0.1 parts of a mixture monomer of dimethyl (dimethylamino) vinyl silane and allyl trimethyl silane in a mass ratio of 1:2, 3 parts of methoxy polyethylene glycol acrylate, and then added 20 parts of deionized water, mixed evenly, and 0.05 parts of ammonium persulfate initiator were added to react for 2 hours, cooled naturally to room temperature, and the pH of the mixture was adjusted to 6 with 50wt.% of industrial alkali to obtain a polymerization-grade high-efficiency suspension stable emulsification thickening component.

[0071] S3. Preparation of water-based anticorrosive coating with photoelectric cathode protection: 60 parts of water-based epoxy resin emulsion (commercially available) film-forming material, 20 parts of synthetic polymer-grade high-efficiency suspension stabilizing thickening component, 5 parts of deionized water, 1.5 parts of a mixture of YT-50B high-efficiency defoamer and DL-272 water-based defoamer in a mass ratio of 1:2, 1 part of water-based emulsion leveling agent 2020, and 1.5 parts of KH-570 were added to the container in sequence, and dispersed at a high speed at a stirring rate of 200 r / min for 0.5 h. Then add 8 parts of nano CeO2 / FeWO4 / CdIn2S4 photocathode protection component, 0.5 parts of polyamide wax powder, and 0.1 parts of cationic guar gum powder, and disperse them at a high speed at a stirring rate of 300r / min for 1h. Add 10 parts of CYDHD-220 and CYDHD-593 mixed curing agent with a mass ratio of 1:1 within 2h before use, and stir at a rate of 120r / min for 1h to obtain a water-based anti-corrosion coating with photocathode protection performance.

[0072] Embodiment 2:

[0073] Preparation of S1, CeO2 / FeWO4 / CdIn2S4 Photocathodic Protection Components

[0074] S11, 2.5 parts of 2M Ce(NO3)3 solution and 2.5 parts of 2M NaOH solution were mixed, 0.15 parts of sodium dodecyl sulfate were added, and the mixture was heated to 100°C for solvent thermal reaction for 2.5 hours. The obtained powder was washed with deionized water 3 times and anhydrous ethanol 3 times, and then the solid was vacuum sintered at 130°C for 2 hours to obtain CeO2 nanopowder with a particle size of 80nm;

[0075] S12. Add 3 parts of 3M Fe(NH4)2·(SO4)2·6H2O solution to 3 parts of 3M Na2WO4·2H2O aqueous solution and mix well. Add 0.02 parts of 1M NaOH solution to adjust the pH of the mixture to 9.0. Place the reaction mixture in a high-pressure reactor at 170°C for 9 hours, filter the obtained slurry, wash with deionized water 4 times, and vacuum dry at 70°C for 5 hours to obtain nano-FeWO4 powder with a particle size of 75 nm.

[0076] S13, 30 parts of the nanomaterials obtained from S1 and 30 parts of S2 are ultrasonically suspended in 70 parts of anhydrous ethanol to obtain a suspension A.

[0077] S14, 8 parts of InCl3.4H2O and 5 parts of Cd(NO3)2·4H2O were dissolved in 40 parts of deionized water and stirred evenly, 15 parts of thiosemicarbazide were added, and 0.25 parts of methylallyl-propyl trimethoxysilane and 0.02 parts of lauryl alcohol polyoxyethylene ether were added and stirred for 1.5 hours to obtain a milky white suspension B, and then the suspension A obtained in step S3 was added to the suspension B and mixed evenly, and then transferred to a high-pressure reactor and heated to 160°C for hydrothermal reaction for 5 hours. After filtering the obtained solid product, it was washed with anhydrous ethanol 4 times, and the washed solid was vacuum dried at 90°C for 4 hours to obtain a nano-scale CeO2 / FeWO4 / CdIn2S4 photocathode protection anticorrosion reinforced composite material. The particle size is 120nm.

[0078] S2. Preparation of polymer grade high efficiency suspension stable emulsifying thickening component

[0079] 10 parts of methoxy polyethylene glycol MPEG-350, 12 parts of maleic anhydride and 3.5 parts of trimethylolpropane trimethacrylate were weighed by weight, added into a reactor, stirred at 140r / min for 10min at 100°C to fully mix and melt the reactants, 0.2 parts of p-toluenesulfonic acid were added, the temperature was raised to 130°C and reacted for 3h, then 3.5 parts of a mixture of allyl polyoxyethylene polyoxypropylene ether and methyl-allyl polyoxyethylene ether in a mass ratio of 1:1, 0.3 parts of dimethyl (dimethylamino) vinyl silane, 4 parts of methoxy polyethylene glycol acrylate were added, and 30 parts of deionized water were added and mixed evenly, and 0.1 parts of ammonium persulfate initiator aqueous solution were added to react for 3h, naturally cooled to room temperature, and the pH of the mixture was adjusted to 7 with 60wt.% of industrial alkali to obtain a non-ionic surface active, efficient, suspending, stable and emulsifying thickening component.

[0080] S3. Preparation of water-based anticorrosive coating with photoelectric cathode protection:

[0081] In the container, 66 parts of waterborne epoxy resin and waterborne epoxy modified polyurethane (commercially available) in a mass ratio of 1:2, 25 parts of polymer-grade surfactant high-efficiency slurry dispersing and stabilizing thickening component, 10 parts of deionized water, 2 parts of a mixture of Foamaster MO 2134 defoamer and TEGO AIREX 902W defoamer in a mass ratio of 1:3, 1.5 parts of a mixture of BYK-306 and BYK-333 in a mass ratio of 1:2, and adhesion promoter KH-560 were added in sequence. 1.8 parts; disperse at a high speed of 250r / min for 1h, then add 10 parts of nano CeO2 / FeWO4 / CdIn2S4 photocathode protection component, 1.0 part of polyamide wax powder, and 0.2 part of cationic guar gum powder, and disperse at a high speed of 350r / min for 1.5h, and add 15 parts of diethylenetriamine curing agent within 2.5h before use, and stir at a rate of 150r / min for 1.5h to obtain a water-based anti-corrosion coating with photocathode protection performance.

[0082] Experimental Example 3:

[0083] Preparation of S1, CeO2 / FeWO4 / CdIn2S4 nano-photocathode protection components:

[0084] S11, 4 parts of 2M Ce(NO3)3 solution and 4 parts of 2M NaOH solution were mixed, 0.2 parts of sodium dodecyl sulfate were added, and the mixture was heated to 110°C for solvent thermal reaction for 3 hours. The obtained powder was washed with deionized water 4 times and anhydrous ethanol 4 times, and then the solid was vacuum sintered at 140°C for 3 hours to obtain CeO2 nanopowder with a particle size of 160nm;

[0085] S12. Add 4 parts of 3M Fe(NH4)2·(SO4)2·6H2O solution to 4 parts of 3M Na2WO4·2H2O aqueous solution and mix well. Add 0.035 parts of 1M NaOH solution to adjust the pH of the mixture to 9.0. Place the reaction mixture in a high-pressure reactor at 180°C for 10 hours, filter the obtained slurry, wash with deionized water 5 times, and vacuum dry at 80°C for 5 hours to obtain nano-FeWO4 powder with a particle size of 130 nm.

[0086] S13. Ultrasonic suspension of 40 parts of nanomaterials obtained from S1 and 40 parts of S2 in 100 parts of anhydrous ethanol to obtain suspension A.

[0087] S14, dissolve 12 parts of InCl3.4H2O and 6 parts of Cd(NO3)2.4H2O in 50 parts of deionized water and stir evenly, add 18 parts of thiosemicarbazide, add 0.4 parts of methylallyl-propyl trimethoxysilane, and 0.04 parts of lauryl alcohol polyoxyethylene ether and stir for 2 hours to mix evenly, and obtain a milky white suspension B, then add the suspension A obtained in step S3 to the suspension B and mix evenly, transfer to a high-pressure reactor and heat to 180°C for hydrothermal reaction for 5 hours, filter the obtained solid product, wash it 5 times with anhydrous ethanol, and vacuum dry the washed solid at 90°C for 4.5 hours to obtain a nano-scale CeO2 / FeWO4 / CdIn2S4 photocathode protection anticorrosion reinforced composite material. The particle size of CeO2 / FeWO4 / CdIn2S4 is 220nm.

[0088] S2. Preparation of polymer-grade efficient suspension stable emulsifying thickening component: 12 parts of methoxy polyethylene glycol MPEG2000, 15 parts of maleic anhydride, and 4 parts of trimethylolpropane trimethacrylate were weighed by weight, added into a reactor and stirred at 180 r / min for 10 min at 110°C to fully mix and melt the reactants, 0.4 parts of p-toluenesulfonic acid were added, the temperature was raised to 130°C and the reaction was carried out for 4 hours, and then 4 parts of allyl polyoxyethylene polyoxypropylene ether and methyl-allyl polyoxyethylene polyoxypropylene ether in a mass ratio of 1:1 were added. A mixture of ethylene oxide, 0.6 parts of a mixture of methacryloxypropyltrimethoxysilane and dimethyl (dimethylamino) vinyl silane in a mass ratio of 1:3, 4 parts of methoxy polyethylene glycol acrylate, and then 35 parts of deionized water are added and mixed evenly, and 0.15 parts of an aqueous solution of ammonium persulfate initiator is added to react for 3.5 hours, and the mixture is naturally cooled to room temperature. After the pH value of the mixture is adjusted to 6.0 with 60wt.% of industrial alkali, a polymerization-grade non-ionic surface active, efficient suspension stable emulsifying thickening component is obtained.

[0089] S3. Preparation of a water-based anticorrosive coating with photoelectric cathode protection: 65 parts of a film-forming substance of a mixture of water-based epoxy resin and water-based epoxy acrylic emulsion in a mass ratio of 1:10, 15 parts of deionized water, 25 parts of a synthetic polymer-grade high-efficiency suspension stabilizing thickening component, 2 parts of a mixture of Foamaster MO 2134 defoamer and DL-272 water-based defoamer in a mass ratio of 1:3, 1:3 of TEGO4100 leveling agent and Glide 1.5 parts of 450 leveling agent mixture; 1.5 parts of adhesion promoter KH-560, high-speed dispersed at a stirring rate of 260r / min for 1.0h, then added with 15 parts of nano CeO2 / FeWO4 / CdIn2S4 photocathode protection component, 1.0 parts of polyamide wax powder, 0.4 parts of cationic guar gum powder, high-speed dispersed at a stirring rate of 400r / min for 1.5h, and within 3h before use, add 13 parts of diethylenetriamine and T31 mixed curing agent in a mass ratio of 1:1, and stir at a rate of 180r / min for 1.5h to obtain a water-based anti-corrosion coating with photocathode protection performance.

[0090] Embodiment 4:

[0091] Preparation of S1, CeO2 / FeWO4 / CdIn2S4 nano-photocathodic protection material components

[0092] S11, 5 parts of 2M Ce(NO3)3 solution and 5 parts of 2M NaOH solution were mixed, 0.2 parts of sodium dodecyl sulfate were added, and the mixture was heated to 120°C for solvent thermal reaction for 3 hours. The obtained powder was washed with deionized water 4 times and anhydrous ethanol 4 times, and then the solid was vacuum sintered at 150°C for 3 hours to obtain CeO2 nanopowder with a particle size of 200nm;

[0093] S12. Add 6 parts of 3M Fe(NH4)2·(SO4)2·6H2O solution to 6 parts of 3M Na2WO4·2H2O aqueous solution and mix well. Add 0.05 parts of 1M NaOH solution to adjust the pH of the mixture to 9.5. Place the reaction mixture in a high-pressure reactor at 180°C for 12 hours, filter the obtained slurry, wash with deionized water 5 times, and vacuum dry at 80°C for 6 hours to obtain nano-FeWO4 powder with a particle size of 150nm.

[0094] S13, 50 parts of the nanomaterials obtained from S1 and 50 parts of S2 are ultrasonically suspended in 120 parts of anhydrous ethanol to obtain a suspension A.

[0095] S14, 15 parts of InCl3.4H2O and 8 parts of Cd(NO3)2.4H2O were dissolved in 60 parts of deionized water and stirred evenly, 20 parts of thiosemicarbazide were added, and 0.5 parts of methylallyl-propyl trimethoxysilane and 0.05 parts of lauryl alcohol polyoxyethylene ether were added and stirred for 2 hours to obtain a milky white suspension B, and then the suspension A obtained in step S3 was added to the suspension B and mixed evenly, and then transferred to a high-pressure reactor and heated to 190°C for hydrothermal reaction for 6 hours. After filtering the obtained solid product, it was washed with anhydrous ethanol for 5 times, and the washed solid was vacuum dried at 100°C for 5 hours to obtain a nano-scale CeO2 / FeWO4 / CdIn2S4 photocathode protection anticorrosion reinforced composite material. The particle size of CeO2 / FeWO4 / CdIn2S4 is 280nm.

[0096] S2. Preparation of polymer-grade efficient suspension stable emulsifying thickening component: 15 parts of methoxy polyethylene glycol MPEG1000, 20 parts of maleic anhydride, and 5 parts of trimethylolpropane trimethacrylate were weighed by weight, added into a reactor, stirred at 200 r / min for 20 min at 120°C to fully mix and melt the reactants, 0.5 parts of p-toluenesulfonic acid were added, the temperature was raised to 140°C for reaction for 5 h, and then 5 parts of allyl polyoxyethylene polyoxypropylene ether and methyl- To an allyl polyoxyethylene ether mixture, 1.3 parts of methacryloxy-propyltrimethoxysilane, 5 parts of methoxy polyethylene glycol acrylate, and then 40 parts of deionized water are added, mixed evenly, and 0.2 parts of an aqueous solution of ammonium persulfate initiator is added to react for 4 hours, naturally cooled to room temperature, and the pH value of the mixture is adjusted to 7 with 55wt.% of industrial alkali to obtain a polymerization-grade, non-ionic surface active, highly efficient, suspending, stable, and emulsifying thickening component containing an organosilicon surface enhancer and polyoxyethylene polyoxypropylene ether alcohol.

[0097] S3. Preparation of water-based anticorrosive coating with photoelectric cathode protection:

[0098] Take 16 parts of the photocathode protection component CeO2 / CdIn2S4 / Bi2S3, add 70 parts of a mixture of water-based epoxy modified polyurethane and water-based epoxy resin emulsion in a mass ratio of 1:15, 30 parts of a polymer-grade surfactant high-efficiency slurry dispersion stabilization thickening component, 3 parts of a mixture of DL-14 and HY-1040A defoamers in a mass ratio of 1:4, 2 parts of a mixture of BYK-306 and water-based coating leveling agent 2020 in a mass ratio of 1:1, and 3 parts of KH-550 adhesion promoter; disperse at a high speed at a stirring rate of 300r / min for 2h, and then add the nano photocathode protection component CeO2 / FeWO4 / CdIn2S4 16 parts, 2 parts of polyamide wax powder, 0.5 parts of cationic guar gum powder, disperse at a high speed of 500r / min for 2 hours, and add 50 parts of curing agent triethylenetetramine within 5 hours before use, and stir at a rate of 300r / min for 2 hours to obtain a water-based anti-corrosion coating with photocathodic protection properties.

[0099] Comparative Example 1: The photocathode protection component of Comparative Example 1 contains only cerium oxide and no FeWO4 / CdIn2S4 component. The other formulation conditions are exactly the same as those of Example 4.

[0100] Comparative Example 2: In Comparative Example 2, the photocathode protection component only contains CeO2 / FeWO4, and the other formulation conditions are exactly the same as those in Example 4;

[0101] Comparative Example 3: No photocathode protection component is added, and other formulation conditions are exactly the same as those of Example 4;

[0102] Comparative Example 4: No synthetic polymer-grade high-efficiency suspension stable emulsifying thickening component was added, and only an equal mass of commercially available common suspension agent sodium polymethacrylate was added, and other formulation conditions were exactly the same as those in Example 4;

[0103] Comparative Example 5: without adding polyamide wax powder and cationic guar gum powder, other formula conditions are exactly the same as those in Example 4;

[0104] Preparation of coating samples: 304 stainless steel plates were polished with 400 mesh, 600 mesh, 800 mesh and 1500 mesh respectively until the surface was smooth, and then ultrasonically cleaned with dilute hydrochloric acid, acetone and anhydrous ethanol in turn to obtain pretreated steel plates. Photoelectric cathode protection anticorrosive coating was applied to the surface of the steel plate with a coating apparatus, with a coating thickness of 0.1 μm and cured for 12 hours to obtain coating samples.

[0105] Test the basic performance and anti-corrosion performance of the coating according to the national standard: Test the solid content of the coating with reference to the test method of national standard GB-1725-79. Through experimental debugging, the solid content (%) of the anti-corrosion coating in the above embodiments is about 52%. Test the hardness of the coating with reference to GB / T6739-2006 "Paints and varnishes: Determination of coating hardness by pencil method". Test the salt water resistance of the coating with reference to GB / T10834-2008 "Determination of salt water resistance of ship paint: salt water and hot salt water immersion method", test the adhesion performance of the coating with reference to GB / T 9286-1998 "Paints and varnishes: Scratching test of coatings", and test the salt spray resistance of the coating with reference to GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes".

[0106] Test example

[0107] Table 1: Performance test of anti-corrosion coating with photoelectric cathodic protection performance

[0108]

[0109] Generally speaking, the larger the negative value of the optical open circuit potential (OCP) after the coating is coupled with the steel plate under sunlight, the stronger the cathode polarization of the coating is, and the better the photoelectric cathode protection effect on the steel plate is. As can be seen from Table 1, the hardness of Examples 1-4 is relatively high, reaching more than 3H, indicating that the surface strength is relatively high; its adhesion is more than 5.6Mpa, indicating that it has good bonding performance with the steel plate substrate and will not fall off the steel plate; and under accelerated corrosion conditions, its salt water resistance is greater than 300d, and the salt spray resistance test is greater than 720h; both are far higher than the national standard, indicating that it has excellent anti-corrosion performance. The optical OCP values ​​of the coating after coupling with 304 stainless steel under sunlight are all below -0.65V, which is lower than the self-corrosion potential of stainless steel -0.215V, indicating that the photoelectric cathode protection type anti-corrosion coating prepared by Examples 1-4 of the present invention has excellent photoelectric cathode protection performance, good mechanical properties and anti-corrosion efficiency.

[0110] It can be seen from Comparative Example 1-2 relative to Experimental Example 4 that its hardness is reduced, adhesion is deteriorated, and salt spray resistance time is reduced, while the rate of decrease of the open circuit potential value under the light state is reduced, indicating that the performance of the ternary nano-CeO2 / FeWO4 / CdIn2S4 composite material is better than that of a single CeO2 or a binary CeO2 / FeWO4 composite material;

[0111] In terms of photocathode protection and improving the physical properties of coatings, CeO2 / FeWO4 / CdIn2S4 can enhance the built-in electric field and photoelectric conversion efficiency of the heterojunction, give full play to the synergistic advantages of the three single materials, improve the anti-corrosion performance and photocathode protection effect of the photocathode protection material, and reach a technical level that cannot be achieved by a single material or binary composite material.

[0112] Comparative Example 3 is a water-based anticorrosive coating prepared without adding CeO2 / FeWO4 / CdIn2S4 composite material as an anticorrosive component. It can be seen that its hardness is poor, adhesion is significantly reduced, salt water resistance, salt spray resistance time is shortened, and especially its OCP value is almost 0, indicating that its physical properties and anticorrosive performance are poor, and more importantly, the photoelectric cathode protection function is basically lost.

[0113] CeO2 / FeWO4 / CdIn2S4 composite materials, as nano-inorganic materials, can fill the pinholes of water-based coatings, enhance the hardness and anti-corrosion performance of the coatings, and at the same time, water-based coatings can also protect the photoelectric cathode protection materials to prevent corrosion media. Therefore, coatings that do not contain photoelectric cathode protection materials have poor physical properties and anti-corrosion properties, and basically have no photoelectric cathode protection effect.

[0114] Comparative Example 4 is a coating performance in which no synthetic polymer-grade high-efficiency suspension stable emulsification thickening component is added relative to Example 4, and only an equal mass of commercially available common suspension agent sodium polymethacrylate is added. It can be seen that the coating of Comparative Example 4 has decreased hardness, decreased adhesion, and the worst salt water resistance and salt spray resistance among all coatings. The open circuit potential value under light is also low, indicating that the suspension stable emulsification thickening component is very important for improving the dispersibility of cathode protection materials, reducing the interfacial tension of organic and inorganic components, improving the wettability of coatings, and enhancing their physical properties, mechanical properties and corrosion resistance. This further illustrates the importance of the polymer-grade high-efficiency suspension stable emulsification thickening component in the present invention.

[0115] Comparative Example 5 is a coating without polyamide wax powder and cationic guar gum powder. The polyamide wax powder and cationic guar gum powder have both the corrosion inhibition effect of the corrosion inhibitor on the metal and the suspension stability of the coating, which helps to further improve the comprehensive performance of the coating. Without the addition of polyamide wax powder and cationic guar gum powder, there is no synergy with the polymer-grade high-efficiency suspension stable emulsification thickening component and the organic coating, so that the coating performance of Comparative Example 5 is far inferior to that of Example 4.

[0116] Summary: The present invention firstly realizes the

[0117] Preparation of CeO2 / FeWO4 / CdIn2S4 heterojunction photoelectric cathode protection composite materials. Under the action of efficient suspension stable emulsification thickening components, the interfacial tension of the photoelectric cathode protection inorganic components is eliminated, so that they are evenly dispersed in the water-based polymer film-forming material emulsion, reducing their aggregation and agglomeration to increase the compatibility of the coating, and preparing photoelectric cathode protection anti-corrosion coatings. In the dark state, the composite materials are used to fill the micropores of the water-based resin film-forming material to enhance its density, improve the physical barrier and mechanical properties of the coating, and perform photoelectric cathode protection and coating protection on the steel plate under light. At the same time, polyamide wax powder and cationic guar gum are added to inhibit corrosion and enhance the stability of the coating. Through the synergistic effect of photoelectric cathode protection materials, high-efficiency suspension stable emulsification thickening components, polyamide wax powder and cationic guar gum, defoaming agent, adhesion promoter, leveling agent and water-based polymer emulsion film-forming substances, the coating has excellent photoelectric cathode protection effect, significantly improves the hardness, adhesion, water resistance and salt spray resistance of the existing coating, and realizes the synergistic effect of photoelectric cathode protection and physical barrier. It shows that the photoelectric cathode protection anti-corrosion coating prepared by the present invention has good application prospects.

[0118] Figure 1 OCP test analysis: Testing the OCP of 304SS coupled with different photoanodes under intermittent light is an important method to evaluate the photocathodic protection performance of the photoanode. Figure 1 As shown. When the light is turned on, the OCP values ​​of CeO2, CeO2 / FeWO4 and CeO2 / FeWO4 / CdIn2S4-photoanodes drop rapidly. The coupling potentials of CeO2 / FeWO4 / CdIn2S4- are approximately -0.810V, respectively. 304SS has the most negative coupling potential. Enhanced photocathodic protection is obtained. In the dark state, the open circuit potential of the CeO2 / FeWO4 / CdIn2S4-photoanode after reaching stability is more negative than the coupling potential of CeO2 under both illuminated and non-illuminated conditions. This shows that CeO2 / FeWO4 / CdIn2S4- has provided excellent photocathodic protection for 304SS. It can also be observed from the figure that after several intermittent light cycle tests, the open circuit potential of the CeO2 / FeWO4 / CdIn2S4-photoanode still shows a sensitive photoelectrochemical response over time, proving that the prepared photoanode has good stability.

[0119] Figure 2(a) is the open circuit potential of the composite of waterborne epoxy modified polyurethane and waterborne epoxy resin emulsion mixture coating with different addition amounts of CeO2 / FeWO4 / CdIn2S4 and (b) pure waterborne epoxy modified polyurethane and waterborne epoxy resin emulsion mixture coating. The corrosion resistance of the samples under visible light irradiation was measured. The photoelectric cathodic protection performance of the waterborne coating and the waterborne coating with different addition amounts of CeO2 / FeWO4 / CdIn2S4 on 304SS was tested in 3.5wt.% NaCl solution. It can be seen that the insulating waterborne coating does not show any photoelectric response and has no cathodic protection performance; the OCP potentials of the coatings with different addition amounts of CeO2 / FeWO4 / CdIn2S4 after visible light irradiation are -0.592, -0.628, -0.692 and -0.710V, respectively. Although the photocathodic protection performance of CeO2 / FeWO4 / CdIn2S4 combined with water-based coating is lower than that of pure CeO2 / FeWO4 / CdIn2S4, the composite coating still retains good photoresponsivity. Due to the addition of photocathodic protection fillers, the nanocomposite material generates electrons under visible light irradiation.

[0120] Figure 3 Middle: Tafel polarization curves of 304SS, pure epoxy coating and different addition amounts of CeO2 / FeWO4 / CdIn2S4 / waterborne coating under light and no light conditions. Figure 3 The corrosion potential (E) of 304SS is -0.298V (vs. SCE), and the current density (i) is 5.45μA / cm 2 Under light, the corrosion potential of 304SS with different addition amounts of CeO2 / FeWO4 / CdIn2S4 / waterborne coatings shifted negatively, and the corrosion potential of 10% CeO2 / FeWO4 / CdIn2S4 / waterborne coatings dropped to -0.501 V. Compared with 304SS, i increased by an order of magnitude, indicating that many photoelectrons generated were injected into the 304SS substrate, which can provide photocathodic protection performance for 304SS.

[0121] However, under the condition of no light, the corrosion potential E of different addition amounts of CeO2 / FeWO4 / CdIn2S4 / water-based coatings becomes more positive and the current density is smaller, indicating that these composite coatings have better anti-corrosion performance than the original water-based coatings under no light conditions. It can protect 304SS from corrosion, which may be attributed to the CeO2 / FeWO4 / CdIn2S4 nanofillers in the water-based coatings blocking the micropores of the coatings and increasing or extending the diffusion path of the corrosive ions.

[0122] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A water-based anticorrosive coating with photoelectric cathodic protection performance, characterized in that: The coating comprises two components, A and B, wherein component A comprises the following raw materials in parts by mass: 60-70 parts of aqueous polymer emulsion film-forming substance; 5-20 parts of deionized water; 20-30 parts of polymer grade high-efficiency suspension stable emulsifying thickening component; 10-30 parts of curing agent; 1.5-3 parts of defoaming agent; 1-2 parts of leveling agent; Adhesion promoter 1.5-3 parts; Polyamide wax powder 0.5-2 parts; Cationic guar gum powder 0.1-0.5 parts; The B component is 8-16 parts by mass of CeO2 / FeWO4 / CdIn2S4 photocathode protection component.

2. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The aqueous polymer emulsion film-forming substance is selected from at least one of aqueous epoxy resin, aqueous epoxy-modified polyurethane, aqueous epoxy acrylic emulsion, or a mixed emulsion of two thereof, and the mass ratio of the mixed emulsion is 1:1-1:

15.

3. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The curing agent is selected from one of CYDHD-220, CYDHD-593, triethylenetetramine, diethylenetriamine, T31, or a mixture of two of them, and the mass ratio of the mixture is 1:1-1:

4.

4. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The defoamer is selected from at least one of Foamaster MO 2134 mineral oil defoamer, TEGO AIREX 902W defoamer, YT-50B high-efficiency defoamer, DL-272 water-based defoamer, DL-14 coating defoamer, HY-1040A defoamer and BYK-054 defoamer, or a mixture of two thereof, and the mass ratio of the mixture is 1:1-1:

4.

5. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The leveling agent is an organic silicon leveling agent, selected from at least one of BYK-306, BYK-333 leveling agent, 3322 hyperbranched polyether water-oil universal leveling agent, water-based emulsion leveling agent 2020, TEGO4100 leveling agent and Glide 450 leveling agent, or a mixture of two thereof, and the mass ratio of the mixture is 1:1-1:

4.

6. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The adhesion promoter is selected from at least one of KH-550, KH-560 and KH-570.

7. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The polymer-grade efficient suspension stable emulsifying thickening component is selected from at least one of methoxy polyethylene glycol (MPEG), maleic anhydride, trimethylolpropane trimethacrylate, p-toluenesulfonic acid, sodium dodecyl sulfate, thiosemicarbazide, lauryl alcohol polyoxyethylene ether, ammonium persulfate, unsaturated organic silane monomer, allyl polyoxyethylene polyoxypropylene ether, methyl-allyl polyoxyethylene ether, and methoxy polyethylene glycol acrylate; The methoxy polyethylene glycol (MPEG) is selected from at least one of MPEG-200, MPEG-350, MPEG-750, MPEG-1000 and MPEG-2000, or a mixture of two of them in a mass ratio of 1:

1.

8. The water-based anticorrosive coating with photoelectric cathodic protection performance according to claim 1, characterized in that: The unsaturated organic silane monomer is selected from at least one of dimethyl (dimethylamino) vinyl silane, allyl trimethyl silane, 3-allyloxypropyl trimethoxy silane, methacryloxypropyl trimethoxy silane, vinyl trimethoxy silane, allyl trimethyl silane, 3-allyloxypropyl trimethoxy silane, methacryloxy-propyl trimethoxy silane (KH570), and methyl allyl-propyl trimethoxy silane, or a mixture of two of them in a mass ratio of 1:1-4:

1.

9. A method for preparing a water-based anticorrosion coating with photoinduced cathodic protection performance, applied to a water-based anticorrosion coating with photoinduced cathodic protection performance as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: Preparation of S1, CeO2 / FeWO4 / CdIn2S4 photocathode protection components: S11: 1-5 parts of 2M Ce(NO3)3 solution and 1-5 parts of 2M NaOH solution are mixed, 0.1-0.2 parts of sodium dodecyl sulfate are added, the mixture is evenly mixed, and the mixture is heated to 90-120°C for solvent thermal reaction for 2-3 hours. The obtained powder is washed with deionized water for 3-4 times, and then washed with anhydrous ethanol for 3-4 times. Finally, the powder is vacuum sintered at 120-150°C for 2-3 hours to obtain CeO2 nanopowder with a particle size of 20-200 nanometers. S12: adding 2-6 parts of 3M Fe(NH4)2·(SO4)2·6H2O solution to 2-6 parts of 3M Na2WO4·2H2O aqueous solution and mixing them evenly, adding 0.01-0.05 parts of 1M NaOH solution to adjust the pH of the mixture to 8.0-9.5, placing the reaction mixture in an autoclave, reacting at 160-180°C for 8-12 hours, filtering the obtained slurry, washing it with deionized water for 3-5 times, and vacuum drying it at 60-80°C for 5-6 hours to obtain FeWO4 nanopowder with a particle size of 10-150 nanometers; S13: ultrasonically suspending the CeO2 nanopowder obtained in step S11 and the FeWO4 nanopowder obtained in step S12 in 50-120 parts of anhydrous ethanol in a ratio of 20-50 parts and 20-50 parts to obtain a suspension A; S14: 5-15 parts of InCl3·4H2O and 4-8 parts of Cd(NO3)2·4H2O are dissolved in 30-60 parts of deionized water, 10-20 parts of thiosemicarbazide are added, and then 0.2-0.5 parts of methylallyl-propyltrimethoxysilane and 0.01-0.05 parts of lauryl alcohol polyoxyethylene ether are added, and the mixture is stirred for 1-2 hours to be uniformly mixed to obtain a milky white suspension B; After suspension A is added to suspension B and mixed evenly, the mixture is transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 150-190° C. for 4-6 hours. The obtained solid product is filtered and washed with anhydrous ethanol for 3-5 times. Finally, the solid product is vacuum dried at 80-100° C. for 3-5 hours to obtain a CeO2 / FeWO4 / CdIn2S4 nanocomposite material with a particle size of 80-280 nanometers.

10. The method for preparing a water-based anticorrosive coating having photocathodic protection performance according to claim 9, characterized in that: The method further comprises: S2. Preparation of polymer-grade high-efficiency suspension stable emulsification thickening component: S21: 8-15 parts of methoxy polyethylene glycol (MPEG), 10-20 parts of maleic anhydride and 3-5 parts of trimethylolpropane trimethacrylate are weighed according to weight ratio, added into a reactor, and stirred at 120-200 r / min at 90-120° C. for 5-20 minutes to fully mix and melt the reactants; S22: adding 0.1-0.5 parts of p-toluenesulfonic acid, raising the temperature to 120-140° C. and continuing the reaction for 2-5 hours; S23: then add 3-5 parts of a mixture of allyl polyoxyethylene polyoxypropylene ether and methyl-allyl polyoxyethylene ether in a mass ratio of 1:1, 0.1-1.3 parts of an unsaturated organic silane monomer and 3-5 parts of methoxy polyethylene glycol acrylate, and continue to stir evenly; S24: adding 20-40 parts of deionized water and mixing evenly, then adding 0.05-0.2 parts of ammonium persulfate initiator aqueous solution, and reacting for 2-4 hours; S25: After naturally cooling to room temperature, the pH of the mixture is adjusted to 6-7 with a pH regulator to obtain a polymer-grade high-efficiency suspension stable emulsification thickening component; S3. Preparation of water-based anticorrosive coating with photoelectric cathode protection: S31: 60-70 parts of aqueous polymer emulsion film-forming substance, 5-20 parts of deionized water, 20-30 parts of polymer-grade high-efficiency suspension stable emulsifying thickening component, 10-30 parts of curing agent, 1.5-3 parts of defoaming agent, 1-2 parts of leveling agent, 1.5-3 parts of adhesion promoter, 0.5-2 parts of polyamide wax powder and 0.1-0.5 parts of cationic guar gum powder are added into a container according to the mass parts, and dispersed at a high speed at a stirring rate of 200-300 r / min for 0.5-2 hours; S32: adding 4-12 parts of nanometer photocathode protection component, and dispersing at a high speed of 300-500 r / min for 0.5-2 hours; S33: Add 10-50 parts of curing agent within 2-5 hours before use, and stir at a rate of 120-300 r / min for 1-2 hours to obtain a water-based anti-corrosion coating with photocathodic protection performance.

Citation Information

Cited By

  • A method for preventing corrosion by using photo-induced micro-current to induce steel surface to form compact protective rust layer and coating

    CN122746112A